Mass communication and national security - Martinez, Sandra M.
Mass communication is a vast field that involves the communication of knowledge and information to the people by the help of a medium or channel so that the information can reach the maximum number of recepients. Mass communication is developing very productively day by day, and more and more people getting attached to the fields that involve the chain of mass communication. The people related to the spread of information in this vertical take up topics ranging across several kinds of subjects that may concern any topic in the world. The rate at which the people are accessing the channels of mass communication and getting interactive through it gives ambitious goals to the information providers. They have started to deal in information that is not limited to only petty topics, but the subjects that may even concern national security concern the people residing in a nation. The book focuses on the several employments of mass communication in a the way they can be either be useful in the field of security for a nation or can be misused to deny it.